The Implementation of Spiritual Education through Boarding Education Program at State High School in South Sumatera - Takrip, Muhamad (Edudeena : Journal of Islamic Religious Education, 2023)
Abstract: Spiritual education plays a central role in the holistic development of learners. The focus isn't solely on the intellectual aspect but also encompasses moral development, spiritual values, and wisdom in daily life. This research aims to comprehend the implementation of spiritual education for students through the Boarding Education program at State High School (SMAN) in South Sumatera. It falls under qualitative research, utilizing a case study approach. Data collection methods involve observation, interviews, and documentation. Data analysis techniques employ qualitative data analysis in three stages: data reduction, data display, and conclusion drawing. The research findings indicate that the Boarding Education program in South Sumatera’s SMAN follows the concept of nine house systems: dolphin, dove, eagle, hornbill, Komodo dragon, lion, manta ray, rhinoceros, and shark. Each house is overseen by 4-5 house coordinators. There are three activities within this spiritual program: Quran recitation, Quran memorization, and Islamic discussions. Several Islamic practices are instilled to support the success of this program, such as congregational prayers, a seven-minute lecture after Maghrib prayers, and nurturing character traits within the students. Abstrak: Pendidikan rohani memegang peran sentral dalam pengembangan peserta didik secara holistik. Titik fokus tidak hanya ada pada aspek intelektual saja tetapi juga pada perkembangan moral, nilai-nilai spiritual, dan kebijaksanaan dalam kehidupan sehari-hari. Penelitian ini bertujuan untuk memahami bentuk implementasi pendidikan rohani bagi peserta didik melalui program Boarding Education di SMAN Sumatera Selatan. Penelitian ini termasuk kedalam jenis penelitian kualitatif dengan pendekatan studi kasus. Metode pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Teknik analisa data menggunakan analisa data kualitatif dengan tiga tahapan, yakni reduksi data, paparan data dan penarikan kesimpulan. Hasil penelitian menyebutkan bahwa program Boarding Education yang ada di SMAN Sumatera Selatan ini menggunakan konsep sembilan sistem rumah, yakni lumba-lumba, merpati, elang, rangkong, komodo, singa, mantaray, badak dan hiu. Masing-masing rumah ini dikawal oleh 4-5 house coordinator. Ada tiga kegiatan dalam program kerohanian ini, yakni khotmil quran, tahsin tahfidz al-quran dan diskusi keislaman. Beberapa pembiasaan-pembiasaan islami dilakukan guna mendukung keberhasilan program ini, seperti gerakan sholat berjamaah, kuliah tujuh menit setelah sholat maghrib, serta penanaman sikap-sikap berkarakter yang ada pada diri peserta didik.